2019
DOI: 10.1177/1086296x19877462
|View full text |Cite
|
Sign up to set email alerts
|

Translingual Writing in a Linguistically Diverse Primary Classroom

Abstract: Growing numbers of scholars in composition studies support translingual orientations in their postsecondary writing classrooms. However, translingual orientations are rarely extended to elementary school writers, who are often asked to compose exclusively in Dominant American English. Drawing on theories of translingualism and emergent biliteracy, we use case study methods to examine children’s translingual writing in a highly linguistically diverse second-grade classroom. We pay particular attention to studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 38 publications
0
45
0
Order By: Relevance
“…In response to these challenges, researchers have identified supports for translanguaging in English‐dominant classrooms. This study has primarily focused on literacy learning, and most studies have taken place in elementary classrooms and focus on students' linguistic resources (Daniel et al, 2019; Machado & Hartman, 2019; Ranker, 2009; L. W. Rowe, 2020; Zapata & Laman, 2016). These studies have identified several promising strategies for supporting multilingual and multimodal composing.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In response to these challenges, researchers have identified supports for translanguaging in English‐dominant classrooms. This study has primarily focused on literacy learning, and most studies have taken place in elementary classrooms and focus on students' linguistic resources (Daniel et al, 2019; Machado & Hartman, 2019; Ranker, 2009; L. W. Rowe, 2020; Zapata & Laman, 2016). These studies have identified several promising strategies for supporting multilingual and multimodal composing.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Strategies that invite and leverage multiple languages include modeling multilingual composing (Machado & Hartman, 2019), introducing multilingual mentor texts (Seltzer, 2020; Zapata & Laman, 2016), and leveraging digital tools, including multimodal eBooks and machine translation tools like Google Translate, to mediate heritage‐language use (D. W. Rowe & Miller, 2016; L. W. Rowe, 2020; Vogel et al, 2018). In addition, researchers have found that emphasizing disciplinary reasons for translanguaging can support multilingual and multimodal composing (Canagarajah, 2013; Durán, 2016; García & Kleyn, 2016; L. W. Rowe, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing students’ linguistic knowledge begins with viewing nondominant language practices as assets rather than deficits. For example, Machado and Hartman (2019) found that elementary English learners’ confidence and writing improved when engaging in translanguaging practices that allowed them to draw from their knowledge of all of their languages. Additionally, incorporating linguistic aspects of hip‐hop, such as call‐and‐response, into pedagogy has also been found to improve students’ science learning (Adjapong & Emdin, 2015).…”
Section: Centering Diverse Forms Of Knowledgementioning
confidence: 99%
“…Discussions around whose knowledge matters must extend to the pedagogical approaches that teachers utilize to support learners in using knowledge that is often underappreciated in academic settings. For example, the practice of translanguaging, which seeks to flexibly utilize the multiple languages that multilingual students have, can help learners of all ages develop deeper text comprehension, as well as support their metalinguistic awareness (García & Kleifgen, 2019; Machado & Hartman, 2019).…”
Section: Theoretical Perspectives: Whose Knowledge Matters?mentioning
confidence: 99%